2001
DOI: 10.7589/0090-3558-37.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure and Tear Production in Captive Eland and Fallow Deer

Abstract: Applanation tonometry was used to estimate intraocular pressure (IOP) and Schirmer tear test (STT) I was used to estimate tear production in both eyes of 12 juvenile elands (Taurotragus oryx) and one eye each of 15 Asian fallow deer (Dama mesopotamica). Mean (Ϯ standard deviation) IOP was 14.6 Ϯ 4.0 mm Hg in the eland and 11.9 Ϯ 3.3 mm Hg in the deer. Mean tear production was 18.7 Ϯ 5.9 mm/min in the eland and 10.5 Ϯ 6.5 mm/ min in the deer. The large variation in IOP between two members of the family Bovidae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
3
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 8 publications
(7 reference statements)
6
32
3
1
Order By: Relevance
“…Hence, it is likely that the mechanism driving increased pressure in winter is partial or complete blockage of the trabecular meshwork by the iris folding over it. The pressures obtained here for summer animals of approximately 13 mmHg are similar to those found in other members of the cervidae family [16]. Hence, raised winter pressure of about 18 mmHg is a seasonal deviation from the normal pattern.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, it is likely that the mechanism driving increased pressure in winter is partial or complete blockage of the trabecular meshwork by the iris folding over it. The pressures obtained here for summer animals of approximately 13 mmHg are similar to those found in other members of the cervidae family [16]. Hence, raised winter pressure of about 18 mmHg is a seasonal deviation from the normal pattern.…”
Section: Discussionsupporting
confidence: 83%
“…However, results for the TonoVet‐D calibration are similar to those obtained for dogs 37 . Tono‐Pen XL ® measurements in the pygmy goats are lower than means and ranges reported from most other animals, with the exceptions of Thomson gazelles, impalas, and some birds 29,36,38–55 . Regardless, the range for Tono‐Pen XL ® measurements broadly overlaps with most other animals.…”
Section: Discussionsupporting
confidence: 69%
“…The following mean IOP were reported with applanation tonometry: 19.2 ± 5.9 mm Hg in dogs, 19.7 ± 5.6 mm Hg in cats, 23.3 ± 6.89 mm Hg in horses, 26.9 ± 6.7 mm Hg in dairy cattle, 14.6 ± 4.0 mm Hg in elands, 11.9 ± 3.3 mm Hg in the deers, 13.10 ± 0.35 in llamas, 14.85 ± 0.45 mm Hg in alpacas, 9.35 ± 1.81 mm Hg in Eurasian Eagle owls, 7.6 ± 1.6 mm Hg in Thomson gazelle and 24·9 ± 2·0 mm Hg in male lions (Miller et al, 1990;Gum et al, 1998;Ofri et al, 1999;Ofri et al, 2000;Willis et al, 2000;Ofri et al, 2001;Jeong et al, 2007;Rusanen et al, 2010). Our study showed that the mean IOP of sheep was lower than those of dogs, cats, horses, dairy cattle and lions, although it was higher than in the eland, deers, llamas, alpacas, owls and Thomson gazelle.…”
Section: Discussionmentioning
confidence: 99%